2013
DOI: 10.4103/2278-9626.116022
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety: Prevalence and associated factors

Abstract: Objectives: This study aimed to estimate the prevalence of dental anxiety and examine the socio-demographic associations of dental anxiety among a representative sample of UAE college populations. Materials and Methods: Four hundred and thirteen college students of Sharjah University in the UAE completed Modified Corah’s Dental Anxiety Scale (MDAS) (47% males and 53% females). The survey also included questions in a yes/no format with which respondents rated attributions for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Researchers have used global questions [19], different scales [15,16,24,26] or different DAS score cut-offs to assess DA [21], which may complicate the comparability of these studies with our results. The DAS and MDAS are the most frequently used tools to measure DA in university students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have used global questions [19], different scales [15,16,24,26] or different DAS score cut-offs to assess DA [21], which may complicate the comparability of these studies with our results. The DAS and MDAS are the most frequently used tools to measure DA in university students.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that women are more susceptible to perceived threats or danger, and that they may describe their fears more openly; while men may be more emotionally stoic and hide their anxieties [37]. Nevertheless, some studies found no sex differences [15,23,24] and mentioned cultural characteristics as a possible explanation [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many questionnaires and scales have been established to investigate dental anxiety and fear [27,28,30,32,35,37]. The DAS is perhaps the most commonly used; it is a four-item, multiple-choice questionnaire that assesses the degree of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that younger subjects are more likely to have dental anxiety than are elderly individuals [25,26]. Many researchers have concentrated on studying dental anxiety in university students [27][28][29][30][31][32][33][34][35][36][37], and the incidence of anxiety ranges from 11% to 27.5% among students at different universities globally [38][39][40]. Higher dental anxiety has been reported in non-dental students than in dental students, which might be because of inadequate dental health education, which leads to high dental anxiety among undergraduate students from nondental colleges [27][28][29], and additional decreases in dental anxiety have been revealed among dental students during the course of their dental training [9,41].…”
mentioning
confidence: 99%